Begomoviruses affecting pulse and vegetable crops are unevenly distributed in distinct agroecological zones of the eastern India. Issue 4 (1st February 2021) - Sahu, Bhimeshwari; Dokka, Narasimham; Mahajan, Mahesh M; Sharma, Kailash Chander; Singh, Harvinder Kumar; Marathe, Ashish; Dewangan, Bhagwat P; Mooventhan, Palanisamy; Yele, Yogesh; Sridhar, Jandrajupalli; Kumar, Vinay; Sivalingam, Palaiyur Nanjappan; et al.
Abstract: Intensive cultivation, climate change and host–pathogen dynamics/interaction had led to emergence of viral diseases and vector population, thereby causing significant economic losses. In the present study, extensive surveys were conducted (during 2016–2017) followed with field experiments (2017 and 2019 kharif and 2018 rabi seasons) in the state of Chhattisgarh, India, comprising of three diverse agroecological zones, viz., northern hill zone, central plain zone and southern Bastar plateau zone, for understanding the distribution pattern of viruses and vector populations in prominent pulses and vegetable crops. Field experiments revealed that more than 90% incidence of yellow mosaic disease (YMD) was recorded in mungbean and urdbean, followed by YMD of ridge gourd and bitter gourd, leaf curl disease of tomato (ToLCD) and chilli and yellow vein mosaic disease of bhendi; however, only five per cent YMD was recorded in cow pea. Molecular and sequence analysis of viral genomic components revealed ToLCD in central plain zone of Chhattisgarh was caused by a consortium of begomoviruses, including Tomato leaf curl New Delhi virus (ToLCNDV), Tomato leaf curl Karnataka virus (ToLCKV), and Tomato leaf curl Kerala virus associated with satellite molecules. YMD of mungbean, cow pea and soybean was caused by Mungbean yellow mosaic India virus (MYMIV), while YMD of ridge gourd was caused by ToLCNDV. PCR analysis, using species‐specific primers, of samples representing the three different regions revealed that YMD of mungbean, urdbean and cowpea was positive only for MYMIV and was unevenly distributed, while YMD of ridge gourd, bitter gourd, pumpkin and sponge gourd was positive only for ToLCNDV; however, ToLCD was positive for either ToLCNDV or ToLCKV or both, and some samples were also found associated with betasatellite molecules. Amaranthus and rice bean were identified as non‐host species for the begomoviruses infecting tomato and MYMIV, as observed by surveys in the hot‐spot‐like areas, controlled whitefly transmission as well as agroinoculation. Compilation and analysis of available information on begomoviruses affecting these crops in India suggest that they are unevenly distributed in India. This is the first report of the begomovirus occurrence in pulses and vegetable crops in this agroecologically diverse region.